Dividend and leverage in Indonesian intergenerational family firms - Aldo Santos; Elvira Rindra; Athalia Ariati Hidayat; Yang Elvi Adelina (Jurnal Siasat Bisnis, 2020)
This paper analyzes the relationships between family ownership and family generation toward dividend payout and leverage in publicly listed Indonesian firms from 2012 until 2016. The research contributes to explaining relationship between family generations toward dividend payouts and leverage in Indonesian family firms. Samples gathered by the purposive sampling method and random effect regression results show significant negative and positive relationships between family ownership and dividend and leverage, respectively. Family as the majority shareholder pays a lower dividend while employing additional supervision from creditors received as a result of using leverage as a control mechanism to mitigate agency problems. Research into family generation shows a significant positive relationship between descendant-controlled firms and dividend payout, which is in line with the income needs perspective, but an insignificant relationship for leverage. Limitations regarding information force this study to exclude the percentage of ownership and use only judgment to classify family-owned firms and generational stage. With proven expropriation activities toward minority shareholders, family firms can increase transparency and improve corporate governance practice.